Uso tradicional de plantas medicinales en gestantes y puérperas en comunidades nativas y mestizas de los Cantones El Pangui y Yacuambi - Martinez Cuesta, Erika Jazzmín_ (2024)
Ancestral medicine is knowledge and practice, with multiple benefits in pregnancy and puerperium. The general objective of this research was to determine the traditional use of medicinal plants in pregnant and puerperal women, as well as the specific objectives, to identify the ethnic group that most frequently uses medicinal plants during pregnancy and puerperal period, To characterize the forms of use of medicinal plants in the period of pregnancy and puerperium of women from native and mestizo communities in the cantons of El Pangui and Yacuambi, whose study has a descriptive design, mixed approach, cross-sectional and prospective cohort. The universe consisted of: 400 women, whose sample was 142 women: El Pangui: 120; pregnant: 58 and puerperal: 62. Yacuambi 22; pregnant: 10 and 12 puerperal, applying the survey and obtaining that; in El Pangui, the mestizo population frequently used medicinal plants, in the early puerperium: 16.7%, using chamomile in the highest percentage 21% in the first trimester of gestation, and Paraguay in the early puerperium: 15%. Chamomile was used to relieve abdominal pain in 29%, in the first trimester and in the early puerperium Paraguay: 23% and escancel: 20% were used to increase breast milk production. In Yacuambi, the Saraguro population mostly used medicinal plants, in the third trimester of gestation: 5.8%, with Llantén being the most used in 14% during the second trimester of gestation and in the early puerperium. Plantain was applied to counteract urinary infections: 14%, in the second trimester, and in the early puerperium Paraguay 10%, guayusa and poleo chiquito, both with: 7%, in the immediate puerperium, to increase breast milk. The form of preparation of the medicinal plants in both cantons was as an infusion, concluding that the medicinal plants have curative properties that benefit the pregnant and puerperal population and the general community